Serum levels of vaspin, obestatin, and apelin-36 in patients with nonalcoholic fatty liver disease - ÇELİKEL, ÇİĞDEM; EREN, FATİH; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (W B SAUNDERS CO-ELSEVIER INC, 2011)
The novel adipokines vaspin, obestatin, and apelin-36 are associated with insulin resistance and the components of the metabolic syndrome. We assayed circulating levels of these molecules and examined their association with clinical, biochemical, and histologic phenotypes in patients with nonalcoholic fatty liver disease (NAFLD). Serum levels of vaspin, obestatin, and apelin-36 were assayed by enzyme-linked immunosorbent assay in 91 patients with biopsy-proven NAFLD and 81 controls. We analyzed associations between adipokines and the characteristics of patients with NAFLD using multivariable linear regression models. Univariable analysis showed that concentrations of vaspin and apelin-36 were significantly higher in patients with NAFLD than in controls, whereas no differences in obestatin levels were found. Serum vaspin levels showed a statistically significant association with C-reactive protein (r = 0.378, P < .001) and liver fibrosis scores (r = 0.401, P < .001), whereas apelin-36 levels showed a modest association with homeostasis model assessment of insulin resistance (r = 0.204, P < .01). After stepwise linear regression analysis, serum vaspin levels were the only independent predictor of liver fibrosis scores in patients with NAFLD (beta = 0.37, t = 3.99, P < .01). Serum vaspin levels are raised in patients with NAFLD regardless of potential confounders and represent an independent predictor of liver fibrosis scores. These findings support further investigation of this novel adipokine in metabolic liver diseases. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: METABOLIC SYNDROME; TISSUE DISTRIBUTION; RECEPTOR; ROLES; ADIPOKINES; OBESITY; LIGAND; MICE; APJ